2014
DOI: 10.1128/mcb.00670-13
|View full text |Cite
|
Sign up to set email alerts
|

AMP-Activated Protein Kinase Induces p53 by Phosphorylating MDMX and Inhibiting Its Activity

Abstract: h AMP-activated protein kinase (AMPK) has been shown to activate p53 in response to metabolic stress. However, the underlying mechanisms remain unclear. Here we show that metabolic stresses induce AMPK-mediated phosphorylation of human MDMX on Ser342 in vitro and in cells, leading to enhanced association between MDMX and 14-3-3. This markedly inhibits p53 ubiquitylation and significantly stabilizes and activates p53. By striking contrast, no phosphorylation of MDM2 by AMPK was noted. AMPK-mediated MDMX phospho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
87
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 95 publications
(89 citation statements)
references
References 71 publications
2
87
0
Order By: Relevance
“…Our data indicated that metformin reduced MDMX level and activated p53 to regulate apoptosis-related proteins. It is in accordance with a previous result that metformin phosphorylates and inactivates MDMX to activate p53 in HCT116 colon cancer cells (13). The combination of metformin and flavone markedly inhibited MDMX and activated p53 compared to metformin treatment only.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Our data indicated that metformin reduced MDMX level and activated p53 to regulate apoptosis-related proteins. It is in accordance with a previous result that metformin phosphorylates and inactivates MDMX to activate p53 in HCT116 colon cancer cells (13). The combination of metformin and flavone markedly inhibited MDMX and activated p53 compared to metformin treatment only.…”
Section: Discussionsupporting
confidence: 93%
“…Metformin exerts anti-proliferative activity on glioblastoma cells by inhibiting AKT signaling (11). Metformin induces p53 activity by regulating AMPK/mTOR signaling pathway (10,12) and activates AMPK to phosphorylate and inactivate MDMX, finally results in stabilization and activation of p53 in cancer cells (13). As a major p53 repressor, MDMX overexpresses in many human cancers, which inhibits DNA repair signals and promotes transformation to contribute to tumorigenesis.…”
Section: Introductionmentioning
confidence: 99%
“…Also, the meta bolic sta tus of the cell acts as a sig nal for p53 in duc tion. When cel lu lar ATP lev els de cline, the re sult ing de crease in the ATP/ ADP ra tio ac ti vates adeno sine monophos phate ki nase (AMPK), and AMPK phos pho ry lates p53 on ser ine 15, thus ini ti at ing AMPK de pen dent cell cy cle ar rest [119,120]. AMPK ac ti va tion acts in most cases as a tu mor sup pres sor by in duc ing a cell cy cle ar rest and by in hibit ing the syn the sis of most cel lu lar macro mol e cules.…”
Section: Metabolic Regulation Of Cancer Cell Deathmentioning
confidence: 99%
“…The subsequent inactivation of MDMX is responsible for the enhanced stability and activation of p53, which provokes a cell-cycle checkpoint. 13 Beyond effects on p53, AMPK directly phosphorylates the tumor suppressor tuberous sclerosis complex 2 (TSC2) thus stimulating its GAP activity toward Rheb, which in turn leads to the inactivation of mTORC1 and the inhibition of cell proliferation. 8,14 AMPK also blocks the positive trophic effects of mTORC1 through the direct phosphorylation of regulatory associated protein of mTOR (raptor) (Figure 1).…”
Section: Ampk Orchestrates Autophagy and Cell Proliferationmentioning
confidence: 99%